Modeling urban tree growth as a part of the green infrastructure to estimate ecosystem services in urban planning - Fauk, Tino; Schneider, Petra (Frontiers in Environmental Science, 2023)
Motivation: Planting urban trees is important for urban development. Foliage reflects, scatters, and absorbs incoming shortwave solar radiation, thus reducing the energy flow to the underlying surface, including streets, houses, and humans. Shaded areas, with primarily anthropogenic substrates, are not as heated as nonshaded areas. Subsequently, temperature, radiation and its influence on morbidity of fauna and flora are comparatively lower in these areas. Materials and Methods: Statistical methods were applied to assess the allometric functions of urban trees. The analyzed data were obtained from the tree cadaster of Magdeburg City, Germany, which contains information from 1936 to 2021. As of June 2022, the tree cadaster contained 89,766 trees. The tree species Acer campestre, Acer platanoides, Malus spp., and Quercus robur were subjected to investigation. Nine temperature optimum (TO)/precipitation optimum (PO) scenarios were considered, and their effects on the allometric relationships on the tree species were determined, respectively: 1. TO 17–19°C/PO 450–550 mm, 2. TO 19–21°C/PO 450–550 mm, 3. TO 21–23°C/PO 450–550 mm., 4. TO 17–19°C/PO 550–650 mm, 5. TO 19–21°C/PO 550–650 mm, 6. TO 21–23°C/PO 550–650 mm, 7. TO 17–19°C/PO 650–750 mm, 8. TO 19–21°C/PO 650–750 mm, 9. TO 21–23°C/PO 650–750 mm. Results and Discussion: In six of nine scenarios, a significant correlation was evident for temperature. Water uptake was found to be significant in scenario 6. No significant correlation for competition and breast head diameter growth could be determined in any scenario. Five of the nine scenarios were significantly comparable. While competition was evident as conditionally non-significant (p-value = 0.069 & 0.058), for the elevation forecast in scenarios 3 & 6 only, dependence was evident in all other scenarios. Regarding the crown diameter, temperature was significant in 3 of 9 scenarios. No significant relationship was found for water uptake and competition. Conclusions: No clear abiotic optimum could be identified. Thus, a continuous adjustment of the parameters is necessary to refine the growth functions. Moreover, the growth function adaptation according to the different age phases of trees might be considered on the long term.